Emotional Intelligence as a Key to High Performance Organizations: An Expository Analysis of the Literature (Journal of Organizational Psychology, 2024)
The utility of emotional intelligence has been researched as both a discreet individual ability, and a performance enhancing quality within organizations. This expository analysis synthesizes the existing literature on the value and utility of emotional intelligence within organizations, focusing on enhanced ethics, improvement of leadership capabilities and outcomes, reduction of turnover, enhancement of cross-cultural understanding, reduction of stress, dispute resolution, and employee promotion. The origin and development of emotional intelligence as a behavioral theory is illustrated and its application to the organizational environment is systematically analyzed, with particular note of gaps in the literature and definitional difficulties identified.
Keywords: organizational psychology; emotional intelligence; workplace ethics; employee wellbeing; workplace stressors; employee promotion; organizational leadership